The Implementation of the Cooperative Model Teams Games Tournament (TGT) Assisted by Flannel Board Media to Improve the Beginning Reading Skills of Second Grade Students - Aristarini, Ni Komang; Suardana, I Putu Oka; Sudirman, I Nyoman (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The low reading skills of students is a problem at Grade 2 of SD Negeri 1 Abang Batudinding. Data shows that less than 50% of students achieve the Minimum Competency Standards (KKTP) in Indonesian language lessons. Therefore, there is a need for a method to address the students' low reading skills. The method used is the Teams Games Tournament (TGT) learning model assisted by Flannel Board Media. The purpose of this study is to explain the reading abilities of students in learning using the Teams Games Tournament model with the help of flannel board media for beginner readers, and to understand how the application of the cooperative Teams Games Tournament model assisted by flannel board media can improve the beginner reading results of second-grade students at SD Negeri 1 Abang Batudinding. The subjects of this study were 27 students from Grade 2 at SD Negeri 1 Abang Batudinding. This research is Classroom Action Research (CAR), conducted in two cycles. The research will be considered successful if at least 80% of the total students in the class achieve the completion standard in the final cycle of learning, with a class average of at least 85. The results show that in Cycle I, the average score of students was 68.33, which increased to 80.11 in Cycle II. The percentage of student completeness in Cycle I was 59%, which increased to 93% in Cycle II.